Crown ether modified wide-band gap perovskite solar cell and preparation method thereof

Crown ether modification in wide bandgap perovskite solar cells addresses energy losses by regulating crystallization and enhancing grain quality, resulting in improved efficiency.

CN119233655APending Publication Date: 2024-12-31TSINGHUA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411120238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Wide bandgap perovskites in solar cells suffer from significant energy losses due to halogen phase separation and accelerated crystallization, leading to reduced efficiency.

Method used

Incorporating crown ether into the wide bandgap perovskite layer to interact with metal ions, delaying crystallization, increasing grain size, and optimizing crystallization orientation, thereby improving open circuit voltage and fill factor.

Benefits of technology

The method enhances the efficiency of wide bandgap perovskite solar cells by inhibiting non-radiative recombination and improving carrier transport.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004994857880000081
    Figure BDA0004994857880000081
  • Figure HDA0004994857890000011
    Figure HDA0004994857890000011
  • Figure HDA0004994857890000012
    Figure HDA0004994857890000012
Patent Text Reader

Abstract

The invention provides a wide-band-gap perovskite solar cell modified by crown ether and a preparation method of the wide-band-gap perovskite solar cell. The wide-band-gap perovskite solar cell comprises a bottom electrode layer, an electron transport layer, a wide-band-gap perovskite layer, a hole transport layer and a top electrode layer which are sequentially stacked, the wide-band-gap perovskite layer comprises an active substance and crown ether, the active substance is CsxFA1-x-yMAyPb (I1-z-wBrzClw) 3, x is larger than or equal to 0.1 and smaller than or equal to 0.4, y is larger than or equal to 0.02 and smaller than or equal to 0.05, z is larger than or equal to 0.1 and smaller than or equal to 0.4, w is larger than or equal to 0.02 and smaller than or equal to 0.05, and the forbidden band width of the wide-band-gap perovskite layer is 1.65 eV to 1.90 eV. Effective regulation and control of the crystallization process of the wide-band-gap perovskite layer are achieved, the grain size is increased, the crystallization quality is improved, the crystallization orientation is optimized, non-radiative recombination is restrained, carrier transport is improved, the open-circuit voltage and the fill factor of the wide-band-gap perovskite solar cell are improved, and the cell efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a wide bandgap perovskite solar cell modified by crown ether and a preparation method thereof. Background Art

[0002] Perovskite solar cells have the advantages of high efficiency, low cost, and simple preparation. The current photoelectric conversion efficiency has reached 26.7%. However, single-junction solar cells have efficiency limits because they cannot take into account both the absorption range and thermal losses at the same time, which limits the further reduction of the cost per kilowatt-hour. For this reason, tandem solar cells have become the focus of common concern in academia and industry. By stacking sub-cells with different bandgap widths, they can simultaneously reduce these two main energy losses and achieve a breakthrough in efficiency. Among them, wide-bandgap perovskite solar cells have become the first choice for the top cell of tandem solar cells because of their suitable and adjustable bandgap and excellent photoelectric performance.

[0003] However, compared with general bandgap perovskites, wide bandgap perovskites have significant energy losses, which are reflected in the open circuit voltage and short circuit current of the device. Wide bandgap perovskites usually use a higher ratio of Cs and Br in their composition, which may cause halogen phase separation under light on the one hand, and accelerate their crystallization process on the other hand, resulting in fine grains and increased defect concentration, which seriously affects the efficiency of perovskite solar cells. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a perovskite solar cell having a wide band gap and improving the open circuit voltage and fill factor of the wide band gap perovskite solar cell.

[0005] In one aspect of the present invention, the present invention provides a wide bandgap perovskite solar cell modified by crown ether. According to an embodiment of the present invention, the wide bandgap perovskite solar cell comprises a bottom electrode layer, an electron transport layer, a wide bandgap perovskite layer, a hole transport layer and a top electrode layer stacked in sequence, the wide bandgap perovskite layer comprises an active substance and a crown ether, the active substance is Cs x FA 1-x-y MA y Pb(I 1-z-w Br z Cl w)3, wherein 0.1≤x≤0.4, 0.02≤y≤0.05, 0.1≤z≤0.4, 0.02≤w≤0.05, and the bandgap width (i.e., bandgap) of the wide bandgap perovskite layer is 1.65-1.90 eV. Thus, the crown ether in the wide bandgap perovskite layer combines with the metal ions (lead ions and cesium ions) in the active material, and the two interact with each other to achieve the modification of the active material by the crown ether, and the crystallization process of the perovskite can be effectively delayed during its preparation, that is, the effective regulation of the crystallization process of the wide bandgap perovskite layer is achieved, the grain size is increased, the crystallization quality is improved, and the crystallization orientation is optimized, thereby suppressing non-radiative recombination, improving carrier transport, and ultimately improving the open circuit voltage and fill factor of the wide bandgap perovskite solar cell, and improving the battery efficiency.

[0006] According to an embodiment of the present invention, the crown ether ring of the crown ether contains 12 carbon atoms.

[0007] According to an embodiment of the present invention, the crown ether is at least one of benzo-18-crown-6, dibenzo-18-crown-6, 18-crown-6, aza-18-crown-6, diaza-18-crown-6 and dithio-18-crown-6.

[0008] In another aspect of the present invention, the present invention provides a method for preparing the wide bandgap perovskite solar cell modified by crown ether as described above. According to an embodiment of the present invention, the method for preparing a wide bandgap perovskite solar cell includes the step of preparing a wide bandgap perovskite layer, and the step of preparing the wide bandgap perovskite layer includes: dissolving methylamine chloride, lead chloride, cesium iodide, lead bromide, formamidine iodine, and lead iodide in a first solvent to obtain a perovskite precursor solution; dissolving the crown ether in a second solvent to obtain an anti-solvent; spin-coating the perovskite precursor solution on a substrate to form an initial thin film; during the spin-coating process, dripping the anti-solvent into the center of the initial thin film to obtain the intermediate thin film; annealing the intermediate thin film to obtain the wide bandgap perovskite layer. Thus, in the above preparation method, during the spin coating process of the perovskite precursor solution, the first solvent gradually evaporates or is thrown out, and the solute gradually forms a thin liquid film (i.e., the initial film); after a period of spin coating, an anti-solvent is added to the center of the initial film, and the anti-solvent can remove the first solvent, so that the solute is quickly supersaturated. In this process, the crown ether in the anti-solvent interacts with the metal ions in the film, precipitates crystals, and forms an intermediate film. In this process, the crown ether effectively delays the crystallization process of the perovskite, that is, the crystallization process of the wide-bandgap intermediate film is effectively regulated, the grain size is increased, the crystal quality is improved, and the crystal orientation is optimized; after the spin coating is completed, the intermediate film is heated and annealed, and the residual solvent evaporates at this time, and the intermediate film is transformed into the final phase, that is, the perovskite layer is obtained. Therefore, the above method for preparing the perovskite layer can effectively inhibit non-radiative recombination, improve carrier transport, and ultimately improve the open circuit voltage and fill factor of the wide-bandgap perovskite solar cell, and improve the battery efficiency.

[0009] According to an embodiment of the present invention, in the anti-solvent, the concentration of the crown ether is 0.001 mg / mL to 1 mg / mL.

[0010] According to an embodiment of the present invention, the volume of the anti-solvent added dropwise is 10 μL to 1000 μL.

[0011] According to an embodiment of the present invention, when the anti-solvent is added dropwise, the rotation speed of the substrate is 1000 rpm to 10000 rpm.

[0012] According to an embodiment of the present invention, the first solvent is a DMF:DMSO mixed solvent with a volume ratio of 3:1 to 4:1.

[0013] According to an embodiment of the present invention, the second solvent is at least one of chlorobenzene, toluene, methyl acetate, ethyl acetate, ethyl ether, and anisole.

[0014] According to an embodiment of the present invention, the annealing treatment is performed at a temperature of 100° C. to 150° C. for 10 min to 60 min.

[0015] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0017] Figure 1 3 is an electron microscope scanning image of the perovskite layer in Example 1 and Comparative Example 1.

[0018] Figure 2 3 is a JV curve diagram of the wide bandgap perovskite solar cell prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0019] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0020] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0021] In one aspect of the present invention, the present invention provides a wide bandgap perovskite solar cell modified by a crown ether molecule. According to an embodiment of the present invention, the perovskite solar cell comprises a bottom electrode layer, an electron transport layer, a wide bandgap perovskite layer, a hole transport layer and a top electrode layer stacked in sequence, the wide bandgap perovskite layer comprises an active substance and a crown ether, the active substance is Cs x FA 1-x-y MA y Pb(I 1-z-w Br z Cl w)3, wherein 0.1≤x≤0.4, 0.02≤y≤0.05, 0.1≤z≤0.4, 0.02≤w≤0.05, FA is formamidine, MA is methylamine, and the bandgap width (i.e., bandgap) of the wide bandgap perovskite layer is 1.65~1.90eV, for example, the bandgap width (i.e., bandgap) is 1.65eV, 1.70eV, 1.75eV, 1.80eV, 1.85eV, 1.90eV, etc. It can be seen that the wide bandgap perovskite layer is a wide bandgap structure, which realizes a wide bandgap perovskite solar cell, wherein the crown ether in the wide bandgap perovskite layer is combined with the metal ions (lead ions and cesium ions) in the active material, and the two interact with each other, which can effectively delay the crystallization process of the perovskite during its preparation, that is, the effective regulation of the crystallization process of the wide bandgap perovskite layer is achieved, the grain size is increased, the crystallization quality is improved, and the crystallization orientation is optimized, thereby inhibiting non-radiative recombination and improving carrier transport, and ultimately improving the open circuit voltage and fill factor of the wide bandgap perovskite solar cell, thereby improving the battery efficiency.

[0022] According to some embodiments of the present invention, the crown ether contains 12 carbon atoms on the crown ether ring. Therefore, when the crown ether containing 12 carbon atoms on the crown ether ring is combined with a metal cation, its size is more compatible with the metal cation, which can better improve the crystallization quality of the perovskite and improve the crystal orientation, and is also the most effective in improving the efficiency of the perovskite solar cell. If the number of carbon atoms in the crown ether is more or less, the compatibility of its size with the metal ions lead ions and cesium ions is weakened, which also has a certain adverse effect on the performance of the solar cell.

[0023] According to some specific embodiments of the present invention, the crown ether ring contains 12 carbon atoms, and the specific types of crown ethers include but are not limited to at least one of benzo-18-crown-6, dibenzo-18-crown-6, 18-crown-6, aza-18-crown-6, diaza-18-crown-6 and dithio-18-crown-6. The above crown ethers can most effectively improve the open circuit voltage and fill factor of wide bandgap perovskite solar cells, and better improve the battery efficiency.

[0024] In another aspect of the present invention, the present invention provides a method for preparing the wide bandgap perovskite solar cell modified with crown ether molecules as described above. According to an embodiment of the present invention, the method for preparing a wide bandgap perovskite solar cell includes the step of preparing a wide bandgap perovskite layer, and the step of preparing the wide bandgap perovskite layer includes:

[0025] S100: dissolving methylamine chloride, lead chloride, cesium iodide, lead bromide, formamidine iodine and lead iodide in the first agent to obtain a perovskite precursor solution.

[0026] In some embodiments, the first solvent in this step is a DMF:DMSO mixed solvent with a volume ratio of 3:1 to 4:1. The solute can be dissolved well in the mixed solvent and evaporated in the subsequent spin coating process, which is beneficial to the formation of the film. The amount of the above-mentioned substances can be determined according to the active substance Cs in the perovskite layer. x FA 1-x-y MA y Pb(I 1-z- w Br z Cl w )3 for proportioning and weighing.

[0027] S200: dissolving the crown ether in a second solvent to obtain an anti-solvent.

[0028] In this step, the selection requirements of the crown ether can be as described above, and the crown ether ring of the crown ether contains 12 carbon atoms. In some specific embodiments, the crown ether is at least one of benzo-18-crown-6, dibenzo-18-crown-6, 18-crown-6, aza-18-crown-6, diaza-18-crown-6 and dithio-18-crown-6.

[0029] Furthermore, the second solvent is at least one of chlorobenzene, toluene, methyl acetate, ethyl acetate, ether, and anisole. Thus, the solvent can effectively dissolve the crown ether and act as an anti-solvent in the subsequent spin coating process to remove the solvent without causing adverse reactions with the active substance.

[0030] According to some embodiments of the present invention, the concentration of the crown ether in the antisolvent is 0.001 mg / mL to 1 mg / mL, for example, the crown ether concentration is 0.001 mg / mL, 0.005 mg / mL, 0.01 mg / mL, 0.05 mg / mL, 0.1 mg / mL, 0.5 mg / mL, 1 mg / mL, etc.

[0031] S300: spin-coating the perovskite precursor solution on the substrate to form an initial thin film.

[0032] During the spin coating process, part of the first solvent gradually evaporates or is thrown out, and the solute gradually forms a thin liquid film (i.e., an initial film). The rotation speed during spin coating can be flexibly selected by those skilled in the art according to actual needs, and is not limited here.

[0033] S400: During the spin coating process, an anti-solvent is added dropwise to the center of the initial film to obtain an intermediate film.

[0034] After spin coating for a period of time, an anti-solvent is added to the center of the initial film. The anti-solvent can remove the first solvent, causing the solute to be quickly supersaturated. During this process, the crown ether in the anti-solvent interacts with the metal ions in the film, precipitates crystals, and forms an intermediate film. In this process, the crown ether effectively delays the crystallization process of the perovskite, thereby achieving effective regulation of the crystallization process of the wide-bandgap intermediate film, increasing the grain size, improving the crystallization quality, and optimizing the crystallization orientation.

[0035] According to some embodiments of the present invention, the volume of the anti-solvent added is 10 μL to 1000 μL, such as 10 μL, 50 μL, 100 μL, 200 μL, 300 μL, 400 μL, 500 μL, 600 μL, 700 μL, 800 μL, 900 μL, 1000 μL, etc. It can be seen that a small amount of anti-solvent can effectively achieve the effect without affecting the performance of the active substance.

[0036] According to some embodiments of the present invention, when the anti-solvent is added dropwise, the rotation speed of the substrate is 1000 rpm to 10000 rpm, such as 1000 rpm, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm, 8000 rpm, 9000 rpm, 10000 rpm, etc. Under the above rotation speed conditions, the anti-solvent can be quickly and evenly distributed in the initial film, so that the crown ether interacts with the active substance in the film, and at the same time, the above rotation speed can effectively throw out the solvent and retain the integrity of the film.

[0037] S500: Annealing the intermediate film to obtain a wide bandgap perovskite layer.

[0038] According to an embodiment of the present invention, the temperature of the annealing treatment is 100° C. to 150° C. for 10 min to 60 min. Under the above annealing conditions, a wide bandgap perovskite layer with better performance can be effectively obtained.

[0039] According to an embodiment of the present invention, in the above-mentioned preparation method, during the spin coating process of the perovskite precursor solution, part of the first solvent gradually evaporates or is thrown out, and the solute gradually forms a thin liquid film (i.e., an initial film); after a period of spin coating, an anti-solvent is added to the center of the initial film, and the anti-solvent can remove the first solvent, so that the solute is quickly supersaturated, and the crown ether in the anti-solvent interacts with the metal ions in the film in the process, precipitates crystals, and forms an intermediate film, and in the process, the crown ether effectively delays the crystallization process of the perovskite, that is, the effective regulation of the crystallization process of the wide-bandgap intermediate film is achieved, the grain size is increased, the crystal quality is improved, and the crystal orientation is optimized; after the spin coating is completed, the intermediate film is heated and annealed, and the residual solvent is volatilized at this time, and the intermediate film is transformed into the final phase, that is, a wide-bandgap perovskite layer is obtained. Therefore, the above-mentioned method prepares the perovskite layer, which can effectively inhibit non-radiative recombination, improve carrier transport, and ultimately improve the open circuit voltage and fill factor of the wide-bandgap perovskite solar cell, and improve the battery efficiency.

[0040] According to some embodiments of the present invention, a wide bandgap perovskite solar cell comprises a bottom electrode layer, an electron transport layer, a wide bandgap perovskite layer, a hole transport layer and a top electrode layer stacked in sequence, wherein a method for preparing a perovskite solar cell comprises:

[0041] T100: Conductive glass substrate processing, i.e. bottom electrode layer

[0042] The conductive glass substrate is ultrasonically cleaned with conductive glass cleaning liquid, deionized water, acetone, ethanol, and isopropanol in sequence, and after cleaning, it is blown dry and surface treated with ultraviolet ozone or oxygen plasma. The conductive glass substrate may be an ITO substrate.

[0043] T200: Preparation of electron transport layer

[0044] The tin oxide colloidal dispersion is spin-coated on the treated conductive glass substrate and annealed; after the annealing, ultraviolet ozone or oxygen plasma is used for surface treatment to obtain an electron transport layer.

[0045] T300: Preparation of crown ether modified wide bandgap perovskite layers

[0046] The wide bandgap perovskite layer is prepared by the method of steps S100 to S500.

[0047] T400: Passivation of wide-bandgap perovskite surface

[0048] A solution of a passivating agent (such as phenylethylamine bromide in isopropyl alcohol) is spin-coated onto the surface of the modified wide bandgap perovskite layer.

[0049] T500: Preparation of hole transport layer

[0050] Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) was dissolved in chlorobenzene, tert-butylpyridine (tBP) and Li-TFSI were added to form a precursor, and the precursor was spin-coated on the surface of the passivated wide bandgap perovskite layer.

[0051] T600: Preparation of top electrode layer

[0052] Gold was deposited by vacuum thermal evaporation as the top electrode.

[0053] Example

[0054] Example 1

[0055] (1) Place a 2 cm × 2 cm ITO conductive glass on a polytetrafluoroethylene glass cleaning rack, put it in a glass box, and add conductive glass cleaning solution (diluted to 2% with deionized water), deionized water, acetone, ethanol, and isopropanol in sequence, and ultrasonicate for 15 minutes. After cleaning, blow dry the conductive glass with a nitrogen air gun and treat it with oxygen plasma for 15 minutes.

[0056] (2) Dilute the commercial tin oxide colloidal dispersion with deionized water to 2.5 wt %, take 100 μL and drop it on the treated conductive glass substrate, and spin coat it at 4000 rpm for 30 seconds. After the spin coating, place it on a hot plate and anneal it at 150° C. for 30 minutes. After the annealing, use oxygen plasma treatment for 2 minutes, and transfer it into a nitrogen glove box to obtain a tin oxide electron transport layer.

[0057] (3) The chemical composition of wide bandgap perovskite is Cs 0.21 FA 0.76 MA 0.03 Pb(I 0.82 Br 0.15 Cl 0.03 )3, the required materials and mass are as follows: methylamine chloride (2.8 mg), lead chloride (11.7 mg), cesium iodide (80 mg), lead bromide (115.6 mg), formamidine iodine (187.8 mg), lead iodide (500.2 mg) are dissolved in 1 mL of a DMF:DMSO mixed solvent (i.e., the first solvent) with a volume ratio of 3:1 to obtain a wide band gap perovskite precursor solution; 70 μL of the wide band gap perovskite precursor solution is dripped onto the treated tin oxide substrate and spin-coated at a speed of 5000 rpm for 20 seconds to obtain a primary film; 5 seconds before the end of the spin coating process, a 0.005 mg / ml benzo-18-crown-6 chlorobenzene solution (i.e., the anti-solvent) is quickly dripped onto the center of the primary film, and after the spin coating process is completed, an intermediate film is obtained. After the spin coating process is completed, the intermediate film is placed on a hot plate and annealed at 100°C for 30 minutes to obtain a crown ether-modified wide band gap perovskite layer.

[0058] (4) Weigh 2 mg of phenylethylamine bromide and dissolve it in 1 mL of isopropanol. Take 70 μL and drop it on the surface of the perovskite layer. Spin-coat at 6000 rpm for 1 min.

[0059] (5) Dissolve 72.3 mg of spiro-OMeTAD in 1 mL of chlorobenzene, add 28.8 μL of tBP and 35 μL of Li-TFSI solution (260 mg / ml dissolved in acetonitrile), take 60 μL and drop it on the surface of the passivated perovskite layer, and spin coat it at 4000 rpm for 30 s.

[0060] (6) Finally, a 70 nm thick gold layer was deposited by vacuum thermal evaporation as the top electrode.

[0061] Example 2

[0062] The difference between this embodiment and embodiment 1 is that the crown ether in step (3) is dibenzo-18-crown-6.

[0063] Example 3

[0064] The difference between this embodiment and embodiment 1 is that the chemical composition of the wide bandgap perovskite layer in step (3) is Cs 0.24 FA 0.73 MA 0.03 Pb(I 0.73 Br 0.24 Cl 0.03 )3.

[0065] Example 4

[0066] The difference between this embodiment and embodiment 3 is that the crown ether in step (3) is dibenzo-18-crown-6.

[0067] Example 5

[0068] The difference between this comparative example and Example 1 is that the crown ether in step (3) is 15-crown-5.

[0069] Example 6

[0070] The difference between this comparative example and Example 1 is that the crown ether in step (3) is dibenzo-21-crown-7.

[0071] Comparative Example 1

[0072] The difference between this comparative example and Example 1 is that no crown ether is added as the anti-solvent in step (3).

[0073] Comparative Example 2

[0074] The difference between this comparative example and Example 3 is that no crown ether is added as the anti-solvent in step (3).

[0075] The perovskite layers in Example 1 and Comparative Example 1 were scanned by electron microscope respectively. Figure 1 As shown by Figure 1 It can be seen that compared with Comparative Example 1, the grain size of the wide bandgap perovskite modified with crown ether in Example 1 is increased.

[0076] The performance of the wide bandgap perovskite solar cells prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were tested respectively, and the test parameters are shown in Table 1 below:

[0077] Table 1

[0078]

[0079] Note: Among the crown ether types, B18C6 refers to benzo-18-crown-6, DB18C6 refers to dibenzo-18-crown-6, 15C5 refers to 15-crown-5, and DB21C7 refers to dibenzo-21-crown-7; in the wide-bandgap perovskite layer, component 1 refers to

[0080] Cs 0.21 FA 0.76 MA 0.03 Pb(I 0.82 Br 0.15 Cl 0.03 )3, component 2 refers to Cs 0.24 FA 0.73 MA 0.03 Pb(I 0.73 Br 0.24 Cl 0.03 )3.

[0081] It can be seen from the test results in Table 1 above that due to the modification of the crown ether in the perovskite solar cells in Examples 1 to 4, the crystallization process of the wide bandgap perovskite layer is effectively regulated, the grain size is increased, the crystallization quality is improved, and the crystal orientation is optimized, thereby suppressing non-radiative recombination, improving carrier transport, and ultimately improving the open circuit voltage and fill factor of the wide bandgap perovskite solar cell, and improving the battery efficiency. By comparing Examples 1 to 4 with Examples 5 and 6, it can be seen that when the number of carbon atoms on the crown ether ring of the crown ether is 12, the open circuit voltage and fill factor of the wide bandgap perovskite solar cell can be better improved, and the battery efficiency can be improved.

[0082] The JV curves of the wide bandgap perovskite solar cells prepared in the examples and comparative examples were tested using a digital source meter (2400, Keithley Instruments, USA). The light source was a solar simulator (91192, Oriel, USA). The power density was calibrated to 100 mW / cm by a standard silicon cell. 2 The JV curves of the wide bandgap perovskite solar cells prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 2 As shown by Figure 2 It shows that the open circuit voltage and fill factor of wide-bandgap perovskite solar cells are effectively improved.

[0083] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0084] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.

[0085] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A wide bandgap perovskite solar cell modified with crown ether and a preparation method thereof, characterized in that: The invention comprises a bottom electrode layer, an electron transport layer, a wide bandgap perovskite layer, a hole transport layer and a top electrode layer which are stacked in sequence, wherein the wide bandgap perovskite layer comprises an active substance and a crown ether, wherein the active substance is Cs x FA 1-x-y MA y Pb(I 1-z-w Br z Cl w )3, wherein 0.1≤x≤0.4, 0.02≤y≤0.05, 0.1≤z≤0.4, 0.02≤w≤0.05, and the bandgap width of the wide bandgap perovskite layer is 1.65 to 1.90 eV.

2. The wide bandgap perovskite solar cell according to claim 1, characterized in that: The crown ether ring of the crown ether contains 12 carbon atoms.

3. The wide bandgap perovskite solar cell according to claim 2, characterized in that: The crown ether is at least one of benzo-18-crown-6, dibenzo-18-crown-6, 18-crown-6, aza-18-crown-6, diaza-18-crown-6 and dithio-18-crown-6.

4. A method for preparing a wide bandgap perovskite solar cell modified with a crown ether according to any one of claims 1 to 3, characterized in that: The method comprises the steps of preparing a wide bandgap perovskite layer, wherein the steps of preparing the wide bandgap perovskite layer include: dissolving methylamine chloride, lead chloride, cesium iodide, lead bromide, formamidine iodine, and lead iodide in a first solvent to obtain a perovskite precursor solution; dissolving the crown ether in a second solvent to obtain an antisolvent; Spin coating the perovskite precursor solution on a substrate to form an initial thin film; During the spin coating process, the anti-solvent is added dropwise to the center of the initial film to obtain an intermediate film; The intermediate film is annealed to obtain the wide bandgap perovskite layer.

5. The method according to claim 4, characterized in that In the anti-solvent, the concentration of the crown ether is 0.001 mg / mL to 1 mg / mL.

6. The method according to claim 4, characterized in that The volume of the anti-solvent added dropwise is 10 μL to 1000 μL.

7. The method according to claim 6, characterized in that When the anti-solvent is added dropwise, the rotation speed of the substrate is 1000 rpm to 10000 rpm.

8. The method according to claim 4, characterized in that The first solvent is a DMF:DMSO mixed solvent with a volume ratio of 3:1 to 4:

1.

9. The method according to claim 4, characterized in that The second solvent is at least one of chlorobenzene, toluene, methyl acetate, ethyl acetate, ethyl ether, and anisole.

10. The method according to claim 4, characterized in that The annealing treatment is performed at a temperature of 100° C. to 150° C. for 10 min to 60 min.